2017
DOI: 10.1016/j.pmedr.2017.04.003
|View full text |Cite|
|
Sign up to set email alerts
|

Impact of a brief intervention on cervical health literacy: A waitlist control study with jailed women

Abstract: Jailed women are four-five times more likely to have had cervical cancer compared to women without criminal justice histories. Previous research has shown that an important contributor to cervical cancer risk, and perhaps lack of follow-up, is incarcerated women's low health literacy about broader reproductive health issues. Little work has been done to address this disparity. Thus, the objective of this study was to test the effectiveness of an intervention to improve incarcerated women's cervical health lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(71 citation statements)
references
References 33 publications
(49 reference statements)
2
68
0
1
Order By: Relevance
“…In SHE, we found that only 67% of these women were up-to-date on cervical cancer screening. 16 With older literature showing low rates of up-to-date breast cancer screening in incarcerated women and our recent study finding less than ideal rates of up-to-date cervical cancer screening, it would not be unexpected that women in jail would continue to have low rates of up-to-date breast cancer screening. The objective of our study was to analyze data from the SHE project to determine what proportion of incarcerated women have up-to-date breast cancer mammography since the change in USPSTF recommendations for biennial screening mammograms starting at the age of 50 years.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations
“…In SHE, we found that only 67% of these women were up-to-date on cervical cancer screening. 16 With older literature showing low rates of up-to-date breast cancer screening in incarcerated women and our recent study finding less than ideal rates of up-to-date cervical cancer screening, it would not be unexpected that women in jail would continue to have low rates of up-to-date breast cancer screening. The objective of our study was to analyze data from the SHE project to determine what proportion of incarcerated women have up-to-date breast cancer mammography since the change in USPSTF recommendations for biennial screening mammograms starting at the age of 50 years.…”
Section: Introductionmentioning
confidence: 74%
“…SHE was informed by social and feminist theory, designed to increase cervical health knowledge, reduce barriers encountered by personal beliefs of breast cancer, and improve self-efficacy and confidence navigating the healthcare system. 16 , 17 …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, incarceration exposed women were less likely to receive prenatal care because of not knowing they were pregnant. To the extent that incarceration exposed women have lower levels of gestational and health literacy [ 57 , 58 , 59 , 60 ], these women may be more prone to not receiving adequate prenatal care (particularly during the first trimester) because of lacking knowledge about the early signs of pregnancy. Furthermore, these barriers (keeping pregnancy a secret and not knowing they were pregnant) could be linked to an unintended pregnancy or ambivalence about being pregnant [ 61 ].…”
Section: Discussionmentioning
confidence: 99%